Go Diego go! Diego's Halloween [videorecording (DVD)] - Austin, Jake T. (Jake Toranzo), 1994- (Nickelodeon., 2008)
Help Diego and Freddie the Fruit Bat as they save the llamas, and deliver goodies to all of the animals on Halloween.